A New Zealand White rabbit model of thrombocytopenia and coagulopathy following total body irradiation across the dose range to induce the hematopoietic-subsyndrome of acute radiation syndrome. (3rd December 2021) - Jackson, Isabel L.; Gurung, Ganga; Poirier, Yannick; Gopalakrishnan, Mathangi; Cohen, Eric P.; Donohue, Terez-Shea; Newman, Diana; Vujaskovic, Zeljko
Abstract: Purpose: The purpose if this study was to develop a rabbit model of total body irradiation (TBI) -induced thrombocytopenia and coagulopathy across the dose-range which induces the hematopoietic subsyndrome of the acute radiation syndrome (H-ARS). Methods: Twenty male New Zealand White rabbits were assigned to arms to receive 6-MV of TBI at a dose of 6.5, 7.5, 8.5 or 9.5 Gy. Animals were treated with moderate levels of supportive care including buprenorphine for pain management, antibiotics, antipyretics for rectal body temperature >104.8 °F, and fluids for signs of dehydration. Animals were closelyfollowed for up to 45 days after TBI for signs of major morbidity/mortality. Hematology and serum chemistry parameters were routinely monitored. Hemostasis parameters were analyzed prior to TBI, 2 and 6 hours post-TBI, and at the time of euthanasia. Results: Animals developed the characteristic signs and symptoms of H-ARS during the first-week post TBI. Animals became thrombocytopenic with signs of severe acute anemia during the second week post TBI. Moribund animals presented with petechia and ecchymosis of the skin and generalized internal hemorrhage. Multiorgan dysfunction characterized by bone marrow failure, gastric ileus, acute renal toxicity, and liver abnormalities were common. Severe abnormalities in coagulation parameters were observed. Conclusions: The presentation of bone marrow failure and multiorogan injury associated with ARS in the New Zealand White rabbit model is consistent with that described in the canine, swine, non-human primate, and in humans. The hemorrhagic syndrome associated with the ARS in rabbits is characterized by thrombocytopenia and hemostasis dysfunction, which appear to underlie the development of multiorgan dysfunction following TBI to rabbits. Taken together, the rabbit recapitulates the pathogenesis of ARS in humans, and may present an alternative small animal model for medical countermeasure pilot efficacy screening, dose-finding and schedule optimization studies prior to moving into large animal models of TBI-induced ARS.